2018
DOI: 10.1021/acs.iecr.8b02545
|View full text |Cite
|
Sign up to set email alerts
|

Study on Modification and Sulfur-Resistance Characteristics of Dolomite Catalysts over Wash Oil Catalytic Cracking

Abstract: The 0.5% Ni/1% Fe−dolomite catalyst and 1% Fe−dolomite catalyst were used to explore the wash oil catalytic cracking process on a fixedbed reactor. The experimental results were evaluated by yield distributions of gas, liquid, and solid phases; gas composition distributions; and component varieties of cracked oil. Catalysts were characterized by X-ray diffraction (XRD), thermogravimetric analysis (TG), and an automatic sulfur analyzer. Cracked oil was analyzed by gas chromatography−mass spectrometry (GC−MS). X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Many research groups have extensively studied dolomites because of its highly effective tar conversion. , Corella et al showed that tar content at the gasifier outlet was approximately 40% lower using dolomite compared to natural olivine. Moreover, dolomite was 1.4 times more active than olivine in biomass gasification with air but at the same time dolomite generates 4–6 times more particulates as well as more NH 3 in the product compared to olivine.…”
Section: Catalysts For Biomass Tar Crackingmentioning
confidence: 99%
See 2 more Smart Citations
“…Many research groups have extensively studied dolomites because of its highly effective tar conversion. , Corella et al showed that tar content at the gasifier outlet was approximately 40% lower using dolomite compared to natural olivine. Moreover, dolomite was 1.4 times more active than olivine in biomass gasification with air but at the same time dolomite generates 4–6 times more particulates as well as more NH 3 in the product compared to olivine.…”
Section: Catalysts For Biomass Tar Crackingmentioning
confidence: 99%
“…Boot-Handford and co-authors observed that calcined dolomite was slightly more effective in biomass-derived tar cracking than calcined limestone, converting 98 wt% of the tar at 900 °C. Recently, Yu and co-workers compared 0.5% Ni–1% Fe–dolomite and 1% Fe–dolomite catalyst for the wash-oil catalytic cracking process in a fixed-bed reactor. It was found that 0.5% Ni–1% Fe–dolomite sample exhibited better catalytic activity in the decomposition of aromatic hydrocarbon than 1% Fe-dolomite catalyst sample.…”
Section: Catalysts For Biomass Tar Crackingmentioning
confidence: 99%
See 1 more Smart Citation
“…Although desulfurization is not the main goal of the catalytic cracking, during the process, at least half of the sulfur contained in the FCC regular feedstock turns into hydrogen sulfide (H 2 S), and the sulfur compounds that remain in the liquid products are lighter than the starting ones and can be easily removed in a subsequent hydroprocessing stage. 55 The sulfur distribution among the products depends mainly on the kind of feedstock, catalyst, conversion, and operating conditions, in particular, the contact time. 56 Even in the usual feedstocks of the FCC unit, the investigated STPO contains 11 600 ppm of sulfur in the form of organic compounds (Table 1), such as mercaptans, sulfides, and, the most common ones in our feed, benzothiazoles and dibenzothiophenes.…”
Section: Energy and Fuelsmentioning
confidence: 99%
“…This not only causes waste of resources, but also leads to environmental pollution . The catalytic cracking of gaseous tar before its condensation is an important way to convert it into high value-added products. Y-type zeolites are solid acid catalysts with three-dimensional porous structure and adjustable acidity, and shows good catalytic effect for the upgrading of coal tar. Majka et al used different catalysts to catalyze the hydrocracking of coal tar and found that Y-type zeolites showed better catalytic performance. Yan et al used two different zeolites to upgrade the coal pyrolysis gaseous tar, and found that ultra-stable Y-type zeolites could considerably improve the yield of light aromatics, whereas Al/SBA-15 has little effect on the conversion of gaseous tar.…”
Section: Introductionmentioning
confidence: 99%